Beneficial effects of fingolimod in MS patients with high serum Sema4A levels. - Toru Koda; Akiko Namba; Yuji Nakatsuji; Masaaki Niino; Yusei Miyazaki; Tomoyuki Sugimoto; Makoto Kinoshita; Kazushiro Takata; Kazuya Yamashita; Mikito Shimizu; Toshiyuki Fukazawa; Atsushi Kumanogoh; et al. (PLoS ONE, 2018)
We previously demonstrated that patients with multiple sclerosis (MS) of high serum Sema4A levels are resistant to IFN-β therapy. To further elucidate the role of serum Sema4A as a biomarker for therapeutic stratification in MS patients, it is important to clarify the efficacy of other disease-modifying drugs (DMD) in those with high serum Sema4A levels. Thus, in this study we investigated whether fingolimod has beneficial effects on MS patients with high Sema4A levels. We retrospectively analyzed annualized relapse rate (ARR) and Expanded Disability Status Scale (EDSS) change in 56 relapsing-remitting multiple sclerosis (RRMS) patients who had been treated with fingolimod, including those who switched from IFN-β therapy. The levels of Sema4A in the sera were measured by sandwich ELISA. The implications of Sema4A on the efficacy of fingolimod were investigated by administering recombinant Sema4A-Fc and fingolimod to mice with experimental autoimmune encephalomyelitis (EAE). Retrospective analysis of MS cohort (17 high Sema4A and 39 low Sema4A) demonstrated the effectiveness of fingolimod in those with high serum Sema4A levels, showing reduction of ARR (from 1.21 to 0.12) and EDSS progression (from 0.50 to 0.04). Consistent with this observation, improvement in the disease severity of EAE mice receiving recombinant Sema4A-Fc was also observed after fingolimod treatment. These data suggest that fingolimod could serve as a candidate DMD for managing the disease activity of MS patients with high Sema4A levels.